Merging Economic Forecasts - Ehud Kalai; Ehud Lehrer (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1990)
Under the rational expectation s assumption of Muth, economic agents use their perfect knowledge of the distribution of future prices to compute optimal current actions. In private forecasts equilibrium, intorduced here, agents use subjective in accurate forecasts about future prices to compute optimal current actions. This paper studies the behavior of a group of expected-utility-maximizing, price-taking agents engaged in an infinite horizon dynamic economy. It is shown that in a private forecasts equilibrium, the subjective forecasts must eventually merge to the correct one, leading the agents to a Muth-type perfect forecast equillibrium.
Keywords: 330